Cutaneous Tuberculosis: A Practical Case Report and Review for the Dermatologist - Frankel, Amylynne (Matrix Medical Communications, 2009)
Cutaneous tuberculosis occurs rarely, despite a high and increasing prevalence of tuberculosis worldwide. Mycobacterium tuberculosis, Mycobacterrium bovis, and the Bacille Calmette-Guérin vaccine can cause tuberculosis involving the skin. Cutaneous tuberculosis can be acquired exogenously or endogenously and present as a multitude of differing clinical morphologies. Diagnosis of these lesions can be difficult, as they resemble many other dermatological conditions that are often primarily considered. Further, microbiological confirmation is poor, despite scientific advances, such as the more frequent use of polymerase chain reaction. The authors report a case that illustrates the challenges faced by dermatologists when considering a diagnosis of cutaneous tuberculosis.